Formação sindical de servidores técnico-administrativos das universidades públicas : caso da escola do SINTESPB - Paiva, Cristiano Zenaide (2017)
This dissertation aims to narrate the complex debate to build a trade union school at the Technical and Administrative Servers Union of the Federal University of Paraíba (SINTESPB). Using the participatory method of Paulo Freire, addressing the issue of union education of university servers, from the school's lag of the militancy on subjects that can raise their knowledge to enable them to fight against the capitalist offensive. Based on a collection of bibliographic sources that record the history of the trade union movement, from the birth of the first workers' organizations to the recent history of unionism of public servers in Brazil and of FASUBRA-Union, which organizes trade unions for the servers of Brazilian universities. Union qualification emerged with trade unionism in the mid-nineteenth century, with the great contribution of trade unions currents, among them Marxism, Anarchism, Social Democrats, Lassalians, Proudonians, and many others. In the twentieth century, contributions by Lenin, Losovsky, Gramsci, Demeval Saviani, Paulo Freire, Bonicuore among others, and developed with the struggles of workers, international and national trade union centrals. The search for a school that can become a great lever in the process of acquiring knowledge, in the development of the consciousness itself, for a self-awareness. This dissertation aims to propose the creation of a union school to raise the level of class consciousness of the servers in the process of empowerment and training of their insertion in the social and union struggles, to overcome the problem of low schooling union. Writing in the narrative method, historicizing the class struggle undertaken by the union federation in its existence of almost 40 years of life. Discussing workers struggles to defend the technical-administrative public servers, the defense of the public and free university, public policies among other battles for better living and working conditions. Debating the conceptions about union qualification stimulating the challenge in high complexity context, to structure a program to guide the qualification in this class union school, a political instrument that can fulfill the expected results by raising the level of political consciousness and the capacity to face the transformations in the work world. Towards the struggle for the new socialist society.